Principles of anticancer drug development - Hidalgo, Manuel; Garrett-Mayer, Elizabeth; SpringerLink (Online service). (New York Springer, 2011)
This is a practical guide to the design, conduction, analysis and reporting of clinical trials with anticancer drugs.
Basic biostatistics for the clinical trialist / Elizabeth G. Hill and Elizabeth Garrett-Mayer -- Fundamental concepts in clinical pharmacology / Daniel L. Gustafson and Erica L. Bradshaw-Pierce -- Bioanalycial methods in clinical drug development / Walter J. Loos, Peter de Bruijn and Alex Sparreboom -- Preclinical models for anticancer drug development / Edward A. Sausville -- Phase I clinical trials with anticancer agents / Stephen Leong ... [et al.] -- Phase II trials with anticancer agents / Hui K. Gan, J. Jack Lee and Lillian L. Siu -- Phase III clinical trials with anticancer agents / Wendy R. Parulekar and Daniel J. Sargent -- Pharmacokinetic studies in early anticancer drug development / Alex Sparreboom and Sharyn D. Baker -- Pharmacodynamic studies in early phase drug development / D. Ross Camidge, Robert C. Doebele and Antonio Jimeno -- Prediction of antitumor response / Fred R. Hirsch and Yu Shyr -- Imaging studies in anticancer drug development / David A. Mankoff -- Role of the U.S. Food and drug administration in cancer drug development / Ann T. Farrell, Ramzi N. Dagher and Richard Pazdur -- Early clinical trials with cytotoxic agents / M.J.A. de Jonge and Jaap Verweij -- Challenges and successes in developing effective anti-angiogenic agents / Laura Q.M. Chow and S. Gail Eckhardt -- Targeted therapeutics in cancer treatment / Colin D. Weekes and Manuel Hidalgo -- Cancer chemoprevention / Christopher H. Lieu, William N. William Jr. and Scott Lippman -- Combined modality therapy in cancer management / David Raben and Kyle Rusthoven -- Cancer vaccines / Daniel Laheru -- Optimising the development of antibodies as treatment for cancer / Craig P. Carden, Hendrik-Tobias Arkenau and Johann S. de Bono -- Oligonucleotide therapeutics / Cy A. Stein, Britta Hoehn and John Rossi -- Anticancer drug development in pediatric patients / Lia Gore and Margaret Macy -- Clinical trials in special populations / S. Percy Ivy ... [et al.] -- NCI-sponsored clinical trials / Andriana Papaconstantinou and Janet E. Dancey.
Electronic reproduction.
Keywords: Antineoplastic agents -- Development; Cancer -- Treatment; Clinical Trials as Topic; Antineoplastic Agents -- pharmacokinetics; Neoplasms -- drug therapy; Cancer Vaccines -- therapeutic use